Application of herbicides as growth regulators of emerald Zoysia grass fertilized with Nitrogen - Dinalli, Raíssa Pereira [UNESP]; Buzetti, Salatiér [UNESP]; De Niro Gazola, Rodolfo [UNESP]; De Castilho, Regina Maria Monteiro [UNESP]; De Souza Celestrino, Thiago [UNESP]; Dupas, Elisângela [UNESP]; Filho, Marcelo Carvalho Minhoto Teixeira [UNESP]; Lima, Ronaldo Cintra [UNESP] (Universidade Estadual de Londrina, 2015)
Nitrogen (N) is essential for nutrition and for the maintenance of the intense green color of lawns. However, this element affects shoot growth and, therefore, mowing frequency, which is a key factor of lawn-maintenance costs. Accordingly, this study aimed to evaluate the use of nitrogen fertilization in combination with the use of potential herbicides as growth regulators to promote the maintenance of the high visual (intense green) and nutritional quality of lawns of emerald Zoysia (Zoysia japonica Steud.) grown in Ultisol soil while reducing their leaf growth. The experiment was conducted at the Teaching, Research and Extension Education Farm (Fazenda de Ensino, Pesquisa e Extensão) of São Paulo State University (Universidade Estadual Paulista Júlio de Mesquita Filho, UNESP), Ilha Solteira Campus/São Paulo (SP), from June/2012 to June/2013. The experimental design consisted of randomized blocks with 20 treatments established in a 5 x 4 factorial arrangement with four replicates, including four herbicides (glyphosate, imazaquin, imazethapyr, and metsulfuron-methyl, applied at doses of 200, 420, 80, and 140 g ha-1 active ingredient (a.i.), respectively) and a control (without herbicide), and four N doses (0, 5, 10, and 20 g m-2), split into five applications delivered throughout the year. The following items were evaluated: length, LCI (leaf chlorophyll index), leaf dry matter production and leaf N concentration and the percentage of phytotoxicity on lawn grass shoots. Doses from 10 to 20 g m-2 N provided sufficient N concentrations to maintain the emerald Zoysia. The herbicides metsulfuron-methyl and glyphosate were superior in the control of lawn leaf growth. While the former was phytotoxic, the latter had no effect on the aesthetic quality of the lawn, standing out as an herbicide that may be used at a dose of 200 g ha-1 to regulate the growth of emerald Zoysia.
Keywords: Lawn; Nitrogen fertilization; Zoysia japonica Steud